2009
DOI: 10.1002/sim.3777
|View full text |Cite
|
Sign up to set email alerts
|

Bayesian spatial modeling of disease risk in relation to multivariate environmental risk fields

Abstract: The relationship between exposure to environmental chemicals during pregnancy and early childhood development is an important issue which has a spatial risk component. In this context, we have examined mental retardation and developmental delay (MRDD) outcome measures for children in a Medicaid population in South Carolina and sampled measures of soil chemistry (e.g. As, Hg, etc.) on a network of sites which are misaligned to the outcome residential addresses during pregnancy. The true chemical concentration a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 41 publications
0
18
0
Order By: Relevance
“…The objectives of the current study were to compare two rural and two urban areas identified in our previous research as containing a cluster of ID in children (Cai et al 2011; Kim et al 2009, 2010; Zhen et al 2008, 2009), and to determine, within these sampling areas, whether high populations of racial/ethnic minorities, and individuals with a low income-to-poverty ratio (ITPR), were positively associated with spatially interpolated Pb concentrations at the United States (US) Census 2000 block group level. These groups, both historically and currently, have been disproportionately exposed to environmental contaminants (Brown 1995).…”
Section: Introductionmentioning
confidence: 99%
“…The objectives of the current study were to compare two rural and two urban areas identified in our previous research as containing a cluster of ID in children (Cai et al 2011; Kim et al 2009, 2010; Zhen et al 2008, 2009), and to determine, within these sampling areas, whether high populations of racial/ethnic minorities, and individuals with a low income-to-poverty ratio (ITPR), were positively associated with spatially interpolated Pb concentrations at the United States (US) Census 2000 block group level. These groups, both historically and currently, have been disproportionately exposed to environmental contaminants (Brown 1995).…”
Section: Introductionmentioning
confidence: 99%
“…The effect of knots specificacion in two-dimensional data has not been investigated in depth. Kim et al (2010) performed a sensitivity analysis for the selection of the number and location of the knots and compared the results with the full-rank kriging. They suggest that the results can be very sensitive to the choice of the spatial parameters (if it is choosen to be fixed as suggested in French and Wand (2004)).…”
Section: Spatial Data Modelling With Low-rank Smoothersmentioning
confidence: 99%
“…They suggest that the results can be very sensitive to the choice of the spatial parameters (if it is choosen to be fixed as suggested in French and Wand (2004)). However, the use of lowrank kriging models are very sensitive to the selection of the number and position of the knots, with few knots the separation between them increases and the estimation of the spatial dependence and parameters become difficult (Ruppert et al, 2003;Kim et al, 2010). For the lead concentration levels, we found that the existence of high variability within a few kilometers or even within the same residential property caused difficulties for variogram analysis and the choice of an appropriate covariance structure for the selection of a spatial correlation.…”
Section: Spatial Data Modelling With Low-rank Smoothersmentioning
confidence: 99%
“…This research is motivated by a study of ID cases in children who were born to mothers who were pregnant, and insured by Medicaid, in South Carolina between 1996 and 2002 (Aelion et al 2009a, b; Kim et al 2009, 2010; Liu et al 2010; McDermott et al 2012, 2011; Zhen et al 2008). In our analysis, we included only the first child for each mother.…”
Section: Datamentioning
confidence: 99%
“…Various approaches have been used in the literature to model residential history (Cook et al 2009; Hoffman et al 2010; Kim et al 2009, 2010; Manjourides and Pagano 2011; Van den Hooven et al 2012; Vieira et al 2002, 2005; Wheeler et al 2012). Recently, with the advancement of geographical information systems, it has become easier to obtain point location data, resulting in an increased need for the development of statistical methods appropriate for this type of data.…”
Section: Statistical Modelmentioning
confidence: 99%